Ehlers Danlos sendromu tip 6'lı bir hastada minör travma ile kornea perforasyonu: Ayırıcı tanı ve tedavi - (:unkn) unknown (My University, 2004)
On altı yaşındaki kadın hasta, sol gözünde minör travma sonucu gelişen korneal perforasyon ile kliniğimize başvurdu. Hastaya genel anestezi altında korneal perforasyon onarımı yapıldı. On gün sonra, yara yerinden aköz hümör sızması ve iris prolapsusu gelişmesi yüzünden, 2. bir operasyonda yara yerinin alt kısmı konjunktiva ile örtüldü. Hastanın sağ gözünde de minör travma ile perforasyon onarımı hikayesi, ağır bant keratopati, 360° korneal neovaskülerizasyon ve ön sineşiler mevcuttu. Hastada Ehlers-Danlos Sendromu (EDS) tip 6 (oküler-skolyotik tip) ön tanısı sistemik araştırmalarla doğrulandı. Bu olgu sunumunda, EDS tip 6 ve minör travma ile göz perforasyonu yapabilecek diğer sistemik hastalıklar tartışılmaktadır.

Sixteen year-old female patient applied to our clinic with corneal perforation due to a minor trauma in the left eye. The patient underwent corneal perforation repair under general anesthesia. Then, the corneal wound was covered with conjunctiva at a second operation as there was aqueous leakage and iris prolapsus at the wound site. The patient also had severe band keratopathy, 360° corneal neovascularization and multiple anterior synechia in the right eye with a past history of corneal perforation. The diagnosis of Ehlers Danlos Syndrome (EDS) type 6 (ocular-scoliotic type) was confirmed with systemic work-up. In this case report, Ehlers Danlos syndrome type 6 as well as other connective tissue disorders which may lead to ocular perforations are discussed.
Corneal perforation with minor trauma in Ehlers Danlos syndrome type 6: Differential diagnosis and treatment
Keywords: Göz Hastalıkları